Malformations of the nervous system - Sarnat, Harvey B.; Curatolo, Paolo (Handbook of clinical neurology, 2008)
'Malformations of the Nervous System' describes the advances which have occurred in clinical neurology and the neurosciences, their impact on the understanding of neurological disorders and on patient care.